Interest rates and asset prices: Annaly Capital Management - McDonald, Michael (Henry Stewart Talks, 2015)
Annaly Capital Management overview, Duration & convexity, Calculating changes in asset value, Hedging interest rates, Three scenarios of changes in interest rates